Computer vision based automated mango grading – a review - Supekar, Amruta; Wakode, Madhuri (Journal of Postharvest Technology, 2024)
Mango (Mangifera indica L.) is one of the most famous fruits and is in great demand worldwide. During exports and local mango marketing, quality  assessment of mangoes is crucial. It is achieved by a post-harvest process of mango grading. Quality evaluation based on appearance features like  ripeness, size, shape and defect, directly affect customer satisfaction and thereby vendor’s economic gains. Such appearance based grading is usually  done by humans just by inspection with naked eye. However manual sorting could be inconsistent, inaccurate, time-consuming and labor intensive.  Computer vision based mango grading, will lead to consistent, accurate and reliable sorting. In recent years many researchers have made an attempt  to perform mango classification/grading using image processing and machine learning techniques. A detailed study of such works, performing mango  classification based on grading parameters is done and a precise summary is presented here.
Keywords: Postharvest operation; mango grading; computer vision; machine learning; image processing